2013
DOI: 10.1152/ajpendo.00517.2012
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of developmentally regulated GTP-binding protein-2 increases bone loss

Abstract: The developmentally regulated GTP-binding protein-2 (DRG2) is a novel subclass of GTPbinding proteins. Many functional characteristics of osteoclasts (OC) are associated with small GTPases. We hypothesized that DRG2 affects bone mass via modulating OC activity. Using DRG2 transgenic mice, we investigated the role of DRG2 in bone remodeling. DRG2 overexpression caused a decrease in bone mass and an increase in the number and activity of OC in vivo. DRG2 overexpression increased fusion, spreading, survival, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…To provide insight into the functional roles of DRG2 in mouse development, we report here, for the first time, that DRG2-deficient mice exhibit a significant growth delay and reduced body weight accompanied by defective osteogenesis and a short life span. Interestingly, DRG2 overexpression caused a decrease in bone mass and increases in the number and activity of osteoclasts in vivo in a previous work [31]. Conversely, in micro-CT analyses of DRG2-deficient mice, it was clearly identified that unossified areas were significantly increased in the skull and that bone formation was dramatically reduced in the appendicular skeleton.…”
Section: Discussionmentioning
confidence: 74%
“…To provide insight into the functional roles of DRG2 in mouse development, we report here, for the first time, that DRG2-deficient mice exhibit a significant growth delay and reduced body weight accompanied by defective osteogenesis and a short life span. Interestingly, DRG2 overexpression caused a decrease in bone mass and increases in the number and activity of osteoclasts in vivo in a previous work [31]. Conversely, in micro-CT analyses of DRG2-deficient mice, it was clearly identified that unossified areas were significantly increased in the skull and that bone formation was dramatically reduced in the appendicular skeleton.…”
Section: Discussionmentioning
confidence: 74%
“…Cops3 is an oncogene residing in the human chromosomal region 17p11.2-p12 - the copy number and expression level of Cops3 was significantly associated with the development of osteosarcoma, the most common primary malignancy of bone [29,30]. Drg2 , a GTP binding protein, overexpression of which in transgenic mice leads to increased number and activity of osteoclasts and bone loss [31]. Map2k3 is increased by RANKL, which in turn aids in osteoclastogenesis from bone marrow precursor cells [39].…”
Section: Discussionmentioning
confidence: 99%